Respuesta :

Answer:

[tex] \frac{45 {x}^{3} - 80x}{ 3{x}^{2} + x - 4} ( \frac{1}{3x - 4} + \frac{1}{x} ) = \frac{4(x + 2)}{5x - 8} [/tex]

[tex] \frac{5x(9 {x}^{2} - 16) }{(3x + 4)(x - 1)} ( \frac{x + 3x - 4}{x(3x - 4)} ) = \frac{4(x + 2)}{5x - 8} [/tex]

[tex] \frac{5x(3x + 4)(3x - 4)}{(3x + 4)(x - 1)} ( \frac{4x - 4}{x(3x - 4)} ) = \frac{4(x + 2)}{5x - 8} [/tex]

[tex] \frac{5x(3x - 4)}{x - 1} ( \frac{4(x - 1)}{x(3x - 4)} ) = \frac{4(x + 2)}{5x - 8} [/tex]

[tex]5 = \frac{x + 2}{5x - 8} [/tex]

[tex]x + 2 = 25x - 40[/tex]

[tex]24x = 42[/tex]

[tex]x = \frac{7}{3} = 2 \frac{1}{3} [/tex]